Ultrastructural and morphometric study of bone tissue regeneration dynamics using a combination of octacalcium phosphate with chitosan and ampicillin for osteoplasty - Chelpanova , I.V. (Морфологія / Morphologia / Morfologìâ, 2022)
The relevance of this study is to provide a comprehensive understanding of the dynamics of bone tissue remodeling after the creation of a defect and subsequent filling with an osteoplastic material containing chitosan, a cationic linear polysaccharide. Despite the established clinical use of osteoplastic materials and the unique properties of chitosan, its impact on bone regeneration in the maxillofacial region, its mechanisms and dynamics, remain incompletely understood and require further clarification and detailed investigation. Aim. The aim of this study is to determine the dynamics of histoarchitectural remodeling of bone-ceramic regenerate following the transplantation of octacalcium phosphate in combination with chitosan and ampicillin into an experimental defect in the rabbit mandible. Methods. Adult male rabbits aged 6-7 months and weighing 2.5-3 kg were used for the study. The control group consisted of animals with a bone defect that healed under a blood clot. The experimental group consisted of rabbits in which the bone defect was filled with an osteotropic material containing octacalcium phosphate, chitosan acetate, and ampicillin (OCР-N-Chitosan-Ampicillin). Post-traumatic bone tissue status within the defect area was monitored for 84 days. Ultrastructural changes were studied using scanning electron microscopy. To determine changes in the regenerate composition, three parameters were counted. The data was analyzed using the Student's t-test, and a difference at p < 0.05 was considered statistically significant. Results. The OCР-N-Chitosan-Ampicillin material induced significant regenerative changes in the surface of the lower jaw experimental bone defect that occurred after the injury and correlated with the dynamics of changes in the relative volume of bone tissue, osteoplastic material, and connective tissue in the regenerate. Morphometric analysis of the relative volume of the regenerative components of the experimental defect established a phased nature of the dynamics of the studied changes. The osteocyte lacuno-canalicular system formed following implantation of the material exhibited characteristics of a typical structure. No foci of incomplete osteogenesis were observed. Compared to the control group, in the area of the external bone lamellae after application of the OCР -N-Chitosan-Ampicillin material, the osteons of the regenerate, in terms of structure and geometry, corresponded to the normal bone of the mandibular ramus. Conclusion. In the experimental group of animals where the defect was filled with OCР-N-Chitosan-Ampicillin material, an active increase in the relative volume of bone tissue in the regenerate was observed. This increase followed a similar dynamic trend as the control group, but it was significantly more intense and advanced than the control.